HISTOPATHOLOGICAL ALTERATIONS OF PERMETHRIN IN LIVER AND INTESTINE OF Xiphophorus helleri (PISCES: POECILIIDAE) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2011)
Large-scale application of pesticides poses a risk for our environment. Permethrin is a widely used pesticide but its histopathological effects in fish are not known completely. The objective of this study was to evaluate the effects of permethrin on swordtail fish (Xiphophorus helleri) liver and intestine. A histopathological light microscopy approach was used and the experiments included a control and three treatment groups exposed to 25, 50 and 100 mu g/L permethrin for 30 days. The control group exhibited normal histology and no tissue damage, while in exposed fish, hepatic lesions were characterized by hypertrophy and vacuolization of hepatocytes, disarray of hepatic cord structure, increase of sinusoidal space, atrophy, necrosis, and infiltration of mononuclear leucocytes. Intestinal lesions included invasion of blood cells into the lamina propria and atrophy, oedema of epithelial cells, and fusion of the villi. In both organs, the severity of damages was dose dependent. These results should help to understand the potency of permethrin toxicity on fish and its aquatic environment.
Keywords: Permethrin; pyrethroid; Xiphophorus helleri; histopathology; liver; intestine; FRESH-WATER FISH; CATFISH CLARIAS-GARIEPINUS; ACUTE TOXICITY; PYRETHROID INSECTICIDES; CYPRINUS-CARPIO; OREOCHROMIS-NILOTICUS; CIRRHINUS-MRIGALA; GAMBUSIA-AFFINIS; RAINBOW-TROUT; NILE TILAPIA